Comparison of Ultrasound-Guided Supra-scapular Plus Axillary Nerve Block with Interscalene Block for Postoperative Pain Management in Arthroscopic Shoulder Surgery; A Double-Blinded Randomized Open-Label Clinical Trial - Faiz, Seyed Hamid Reza (Anesth Pain Med, 2021)
BACKGROUND: Post-arthroscopic shoulder surgery pain is severe enough to interfere with initial recovery and rehabilitation. OBJECTIVES: We aimed to evaluate the analgesic effects of postoperative ultrasound-guided suprascapular plus axillary nerve blocks superficial subepidermal axon bundles (SSAB) with interscalene block (ISB) in arthroscopic shoulder surgery. METHODS: In this single-blind randomized, open-label clinical trial, 80 candidates of elective arthroscopic shoulder surgery were randomly allocated to receive either SSAB or ISB at a postoperative care unit. The severity of resting and changing position pain was measured using visual analogue scale (VAS) score at 4h, 8h, 12h, 16h, and 24h, postoperatively. Timing of first opioid request, 24h dose requirement, patients' satisfaction rate, and side effects were also recorded. All registered data were analyzed using SPSS software version 23 for Windows (SPSS, Chicago, IL). RESULTS: Resting and changing position pain scores were comparable between SSAB and ISB groups in the most time intervals. At 12h, moving and resting pain was significantly lower in ISB than SSAB group, while moving pain was more severe in ISB group at 24h assessment. Patient satisfaction scores were comparable between the two groups except for 12h assessment. Time to first analgesic requirement and total dose of 24h opioid requirement were not significantly different between the two groups. CONCLUSIONS: Suprascapular plus axillary nerve block could be an effective and safe alternative for interscalene block for pain management after arthroscopic shoulder surgery.